4-D ERT monitoring of oil spill contamination dynamics and remediation planning in southern Nigeria - Stanley Uchechukwu Eze; Difference Odeyovwi Ogagarue; Juyeon Jeong; Myung Jin Nam; Omafume M. Orji; Williams N. Ofuyah (Academia Environmental Sciences and Sustainability)
4-D Electrical resistivity tomography (ERT) was employed at the Kegbara Dere oil spill site in Ogoniland, Rivers State, southern Nigeria, to monitor the pollution dynamics of the contaminant plume, identify its preferential flow path, and determine target areas for decontamination to optimize remediation planning. Twelve survey lines were executed in a grid at four time points at the spill site. The independent inversion of 3-D datasets displayed acute variations in the apparent resistivity of the contaminants in response to precipitation, and a maximum depth of 41.8 m was imaged. A time-dependent evaluation of 3-D ERT models showed a reduction in the apparent resistivity of the contaminant plume during the rainy season compared to the dry season. This tendency is attributed to the dilution effect of rainfall, which increases the water content of the soil in the wet season. The time-lapse (TL) 3-D datasets were subjected to 4-D simultaneous inversion using a developed in-house algorithm, and the 4-D inversion results were analyzed to show the real-time position of the contaminant plume and the migration flow pathway is oriented to the southwest of the spill site. A maximum depth of 44.0 m was investigated. The 4-D inversion was able to eliminate time-related inversion artifacts to identify the preferential flow path of contaminant plumes at the spill site. This allows the environmental assessment of the target areas for cleanup and decontamination. An investigation of water specimens collected from five boreholes at the spill site revealed an average concentration of total petroleum hydrocarbon for the specimens as 739.51 µg/l, which surpassed the Directorate of Petroleum Resources (DPR) margins (50 and 600 µg/l). The summed polycyclic aromatic hydrocarbons concentration in the specimens was measured at 0.70 µg/l in borehole 1 (BH1), 0.79 μg/l in borehole 2 (BH2), 0.36 μg/l in borehole 3 (BH3), 1.00 μg/l in borehole 4 (BH4), and 1.89 μg/l in borehole 5 (BH5), which are beyond the DPR target margin of 0.15 µg/l. Benzene, toluene, ethylbenzene, and xylene compositions also displayed elevated concentrations in the specimens. The direction of groundwater flow is toward BH4, located southwest of the spill site, indicating the most at-risk receptor area for contamination. The results obtained from the geophysical and geochemical methods showed a strong correlation and have been validated as efficacious tools for environmental monitoring and pollution assessment at contaminated sites. The 4-D inversion proved beneficial for remediation planning and sustainable development, even in the presence of rainfall during the TL surveys.